Strategi Penguatan Karakter Islami Melalui Pendidikan di Pesantren Modern - Abdul Aziz; Eneng Muslihah; Fandy Adpen Lazzavietamsi; Ilzamudin; Rifyal Ahmad Lugowi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
This study aims to analyze the strategy of strengthening Islamic character through education in Islamic boarding schools. Using the library research method, this study examines various sources that discuss the implementation of character education in Islamic boarding schools. The results of the study indicate that habituation methods, such as congregational prayer and post-Maghrib sermons, as well as exemplary behavior from kiai and ustadz, are effective strategies in shaping the character of students. In addition, the study of yellow books and the application of discipline also play an important role in the internalization of Islamic values. Supporting factors include adequate facilities and infrastructure, the figure of kiai as a role model, strict rules, and supervision from ustadz/ustadzah. However, challenges such as the influence of secular culture and modern technology are obstacles in this process. Therefore, it is necessary to adapt character education strategies that are in accordance with the context of the times without ignoring the traditional values ​​of Islamic boarding schools.